BAURAN PEMASARAN (MARKETING MIX) TELUR AYAM KAMPUNG DI KABUPATEN BANYUMAS - Supranoto Supranoto (Fakultas Peternakan Universitas Wijaya Kusuma Purwokerto, 2022)
This study aimed to analyze the marketing mix of native chicken (ayam kampung) eggs in Banyumas Regency, covering product, price, place, and promotion. The research was conducted in Banyumas Regency, Central Java Province, for three months in 2021. The location was purposively selected, given that Banyumas Regency is one of the centers of smallholder native-laying-chicken enterprises and that there is high demand for native chicken eggs in the former Banyumas Residency. The research method was a case study, with data collected through observation and questionnaire-guided interviews. Data sources comprised primary and secondary data. Respondents were selected through purposive sampling, totaling 32 people: 20 native chicken egg farmers and 12 egg traders. Data were analyzed descriptively. The results showed that the average flock size was 285 birds per farmer, with an average production of 138 eggs/day/farmer and a hen-day production (HDP) of 48.5%. Egg weight ranged from 38 to 45 g with white to brownish-cream shells. The price of native chicken eggs ranged from IDR 1,300 to IDR 1,500 per egg, depending on size and quality, which was relatively higher and more stable than that of commercial layer eggs. The distribution channels used were direct (farmer–consumer) and indirect (farmer–collector–retailer–consumer), with marketing reach extending to Banyumas Regency and surrounding areas, including Purbalingga, Cilacap, and Banjarnegara. Promotion was carried out through personal selling, word of mouth, and social media. Native chicken eggs have a special market segment, particularly health-conscious consumers and the herbal medicine (jamu) industry.